Seroepidemiology and antimicrobial susceptibility of Streptococcus pneumoniae isolated from patients with pneumococcal pneumonia - Hamzagić, Farah; Ranin, Jovana; Ranin, Lazar (Medicinski podmladak, 2021)
Seroepidemiology and antimicrobial susceptibility of Streptococcus pneumoniae isolated from patients with pneumococcal pneumonia Author: Farah Hamzagić, Jovana Ranine-mail: hamzagicf98@gmail.comMentor: Full Prof. dr Lazar Ranin, Institute of Microbiology and Immunology, Medical Faculty, University of Belgrade Introduction: Streptococcus pneumoniae is a major cause of community-acquired pneumonia (CAP). In Serbia, conjugate vaccines that contain 10 (PCV-10), or 13 (PCV-13) pneumococcal serotypes were licensed for immunization in 2018.Aim: The aim of this study was to evaluate serotype distribution and antimicrobial susceptibility of S. pneumoniae isolated from patients with pneumococcal pneumonia.  Material and Methods: Isolates of S. pneumoniae were recovered from patients with CAP addmitted to 18 hospitals throughout Serbia from 2012-2020. Confirmation of the identification was performed using LytA gene detection by PCR. Serotyping and antimicrobial susceptibility testing was performed by Quellung reaction and disk diffusion/gradient test, respectively. Interpretation of the susceptibility testing was done according to the current European Committee on Antimicrobial Susceptibility Testing recommendations.Results: During the study period, a total of 100 isolates of S. pneumoniae were collected. Overall, 19 pneumococcal serotypes were identified. The predominant types observed, in order of decreasing frequency, were 3 (37%), 14 (16%), 6B (6%), 7F (5%), 9V (4%), and 4 (4%); further, 2% of the isolates were non-typeable. However, the most common serotype among children